Contribuições para a embriogênese somática indireta em Eugenia involucrata e para a caracterização molecular de indivíduos de Carya illinoinensis - Bittencourt, Larissa (2017)
Due to a raise in forest ecosystem alterations, either by anthropic or natural action, there has been a need for knowledge and conservation of Brazilian forest genetic resources, since environment preservation has a great social and economical interest. Eugenia involucrata DC. (Cerejeira-do-mato), a Brazilian forest fruit species which has been used in projects for the recovery of degraded areas and legal and permanent reservation areas can as well be an alternative income for family agriculture, through the use of its non-timber products. However, besides this species having recalcitrant seeds, which lose viability fast, there is a lack of scientific and technological information that subsidize its sustainable use. Because of this, the present paper aimed at selecting efficient methods of calogenesis induction from leaf explants, addressing indirect somatic embryogenesis and, simultaneously, the improvement of this species in vitro cultivation techniques. In regard to calogenesis in vitro, microbial contamination and callus induction on leaf discs of Eugenia involucrata were assessed and selected, about phenolic oxidation: the combinations of 2,4-dichlorophenoxyacetic acid (2,4-D) and Thidiazuron (TDZ) concentrations, the same way, the embryogenic potential of the calluses formed was assessed, through a histochemical test; sucrose concentrations; the combinations of sucrose and TDZ concentrations; and, also, the reduction of sucrose and 2,4-D and TDZ phytoregulators concentrations. All of them added to MS nutrient medium. As main results, the following stand out: the phenolic oxidation was higher in the presence of 2,4-D, and the combination of 2,4-D and TDZ was not significant in callus formation, only cytokinin, however the presence of auxin in the nutrient medium is essential for calogenesis. The same way, the calluses presented embryogenic potential with a friable aspect and nodular structures; TDZ has influenced the microbial contamination, once in its presence there is a smaller occurrence of bacterial colonies and fungal mycelia. Sucrose and TDZ, when applied in isolation, influenced the formation and quality of the calluses, however, the interaction between them was not significant. The decrease of sucrose and phytoregulators 2,4-D and TDZ did not affect the tested variables. The best combinations of 2,4-D and TDZ for calogenesis on leaf discs of Eugenia involucrata are 5 and 5 μM and 5 and 10 μM, respectively. The most indicated concentration of TDZ is 5 μM, for it being the concentration with which the calluses have an improved quality and, simultaneously, contributes for cost reduction. The most efficient sucrose concentrations for calogenesis are 30 or 90 gL-¹, being that the calluses quality is superior in the bigger one. The calogenic formation on leaf discs of Eugenia involucrata aiming at an indirect somatic embryogenesis is possible.